Phytochemical studies and biological activities of the dichloromethane extract of the peperomia pellucida - Nurhayati, Bidin (Universiti Malaysia Sarawak, UNIMAS, 2008)
A phytochemical and biological activity of Peperomia pellucida (P.pellucida) from the Dichloromethane (DCM) extract is a study to determine the chemical components present in P. pellucida. The percentage yield of the P. pellucida extract was 4.12%. The crude was fractionated into several fractions using Column Chromatography. Then, the combined fractions were purified by the 20 cm x 20 cm TLC plate. The two major chemical components of the separated band from TLC were analyzed by Gas chromatography-Mass Spectrometry (GC-MS). For component 1, one major peak shown at the retention time 6.409 where as the component 2, three major peaks been observed at the retention time of 14.171, 26.828, and 28.292. Ion fragmentation data shown that compound at 14.171 min has the molecular weight equal to 212.3 g/mol. Bioassay was carried out on Artemia salina, Coptotermes spp., Escherichia coli and Staphylococcus aureus. The results of bioassay indicate that the DCM extract has low toxic properties.